Raising a child with autism : a guide to applied behavior analysis for parents - Richman, Shira, 1972- (Jessica Kingsley Publishers, 2001)
Richman explains how parents can adapt ABA for use at home, providing guidance to increase play skills, improve communication and increase independence. The book also covers toilet-training, food selectivity, self-dressing and community outings, and includes an overview of the theory behind ABA as well as a list of resources for further reading.